AN IN-SILICO STUDY ON THYMOMA WITH INHIBITORS FROM PETIOLE AND TENDER COCONUT WATER FROM COCOS NUCIFERA (International Journal of Pharmaceutical Sciences and Drug Research, 2014)
Thymoma is a tumor originating from the epithelial cells of the thymus. Thymoma is an unusual tumor, best known for its association with the neuromuscular disorder myasthenia gravis. When diagnosed, thymomas may be removed surgically. In the rare case of a dangerous tumor, chemotherapy may be used. Health and medicinal applications of tender coconut product get research interest in recent years. The application of edible coconut part is due to the different natural components present in it. This research paper aimed to know the main reported components of coconut i.e., tender coconut water and coconut Petiole for its inhibitory activity against Thymoma. We have chosen target proteins for Thymoma viz RasP21 protein (PDB ID: 4FSS), AKT-1 (PDB ID: 3O96) and BCL-2 (PDB ID: 4AQ3) for our study, it was predicted to be expressed in Thymoma. Docking is frequently used to predict the binding orientation of small molecule drug candidates to their protein targets in order to in turn predict the affinity and activity of the small molecule. Docking study of the target protein was done with natural compounds derived from coconut. The coconut palm (also, cocoanut), Cocos nucifera, is a member of the family Arecaceae (palm family). It is the only accepted species in the genus Cocos. The term coconut can allude to the whole coconut palm, the seed, or the fruit, which, botanically, is a drupe, not a nut. Chemical constituents found in extracts of entire coconut palm. Phytochemicals screened for Glide HTVS docking showed good interaction with the target. The antitumor compound that yielded a fitness score of more than -5 and good toxicity value were further subjected to Molecular dynamics simulation (MDS). L-Histidine can be a good drug considering their binding affinity, glide energy, glide score and toxicity and that could be a potential target for Thymoma. The docking and ADME studies were performed using Schrödinger Suite.